PENGARUH PENERAPAN K-13 TERHADAP SISTEM PEMBELAJARAN SD/MI DI KAB. MADIUN PADA MASA PANDEMI - Fitria Rizqi Y; Ridzo Ayu Safitri; Hani’atul Mukharomah; Meliana Safitri; Darmadi Darmadi (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
The curriculum is very important in educational management. Currently, most schools in Indonesia have implemented the 2013 curriculum as their basic reference. Yet, with a pandemic like this, the implementation of the 2013 curriculum has experienced problems for both teachers and students. Distant learning makes the student center method found in the 2013 curriculum more difficult to implement optimally. In addition, some problems were also felt by teachers, students, and even parents. The purpose of this study is to determine the application of K-13 during the current pandemic, to find out what obstacles faced by SD/MI during the pandemic, and to find out the learning system applied during the pandemic. This study used a qualitative method, namely semi structure interview with teachers/education personnels in several elementary schools in Madiun Regency, especially in South Madiun.